2006
DOI: 10.2337/diacare.29.04.06.dc05-2544
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Fulminant Type 1 Diabetes Associated With Painless Thyroiditis

Abstract: ent, and the herbal combination appears to slowly improve the FBG concentrations over a period of continuous use. Surprisingly, this effect was rapidly reversed when the treatment ceased, as blood glucose retuned to pretreatment levels within 15-20 days. Those subjects who started to take the herbal remedy again after the withdrawal period showed a more rapid decline in their FBG concentrations than when they first started the treatment. It is unclear from this study whether the FBG would return to euglycemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…However, the involvement of T-cell autoimmunity in this disease has also been reported previously (Taniguchi et al 2001(Taniguchi et al , 2005Shimada et al 2002a, b). Moreover, Hamasaki et al (2006) reported that fulminant type 1 diabetes and painless thyroiditis presented simultaneously in a 47-year-old woman without treatment of the immune checkpoint inhibitor. Painless thyroiditis is generally considered to be an autoimmune disorder (Dayan and Daniels 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the involvement of T-cell autoimmunity in this disease has also been reported previously (Taniguchi et al 2001(Taniguchi et al , 2005Shimada et al 2002a, b). Moreover, Hamasaki et al (2006) reported that fulminant type 1 diabetes and painless thyroiditis presented simultaneously in a 47-year-old woman without treatment of the immune checkpoint inhibitor. Painless thyroiditis is generally considered to be an autoimmune disorder (Dayan and Daniels 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Painless thyroiditis is generally considered to be an autoimmune disorder (Dayan and Daniels 1996). Therefore, the case reported by Hamasaki et al (2006) suggested participation of autoimmune mechanisms at the onset of fulminant type 1 diabetes. Occurrence of fulminant type 1 diabetes mellitus was also observed after nivolumab-induced painless thyroiditis in the present case.…”
Section: Discussionmentioning
confidence: 99%